Pengaruh ROA, CR dan DER terhadap Harga Saham Perusahaan Pertambangan Sub Sektor Energi yang terdaftar di BEI Periode 2018 - 2022 - Wardhani, Kadek Ardana Ria; Wulandari, Ni Luh Adisti Abiyoga; Sunny, Milla Permata (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The basis for making investment decisions by investors is based on the published financial reports, apart from that, the analysis that has been carried out can reflect the share price. The factors that influence high or low share prices are return on assets, current ratio, and debt-to-equity ratio. This research aims to determine the influence of Return On Assets, Current Ratio, and Debt To Equity Ratio on Share Prices in Energy Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange in 2018-2022. The population used in this research is the Mining Companies in the Energy Sub Sector which are listed on the Indonesian Stock Exchange in 2018-2022, a total of 21 companies. The number of samples in this study was 105 financial reports which were determined using purposive sampling techniques and tested using multiple linear regression analysis techniques. The results of this research indicate that Return On Assets has a positive effect on stock prices. Current Ratio has no effect on Share Prices and Debt to Equity Ratio has no effect on Share Prices.